2015
DOI: 10.1016/j.niox.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute supplementation of L-arginine and nitrate on endurance and sprint performance in elite athletes

Abstract: This study examined the effects of acute supplementation with L-arginine and nitrate on running economy, endurance and sprint performance in endurance-trained athletes. In a randomised cross-over, double-blinded design we compared the effects of combined supplementation with 6 g L-arginine and 614 mg nitrate against 614 mg nitrate alone and placebo in nine male elite cross-country skiers (age 18 ± 0 years, VO2max 69.3 ± 5.8 ml ⋅ min(-1) ⋅ kg(-1)). After a 48-hour standardisation of nutrition and exercise the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 46 publications
3
32
3
Order By: Relevance
“…2014) and maximal power of inertial-load cycling (Coggan et al 2015) following NO 3 -supplementation, it might be anticipated that any ergogenic effect might be accentuated during the initial phase of all-out sprinting. Indeed, our findings indicate that the greatest improvement in sprint performance (2.3%) occurred over the initial 5 m. Moreover, BR continued to enhance speed between 5 m and 10 m. Together with previous observations of improved sprint performance (Rimer et al 2015;Thompson et al 2015;Sandbakk et al 2015), these findings strengthen the evidence base for using NO 3 -as a nutritional aid to enhance aspects of sprint running performance.…”
Section: The Effect Of Br On Maximal Sprint Running Performancesupporting
confidence: 84%
See 2 more Smart Citations
“…2014) and maximal power of inertial-load cycling (Coggan et al 2015) following NO 3 -supplementation, it might be anticipated that any ergogenic effect might be accentuated during the initial phase of all-out sprinting. Indeed, our findings indicate that the greatest improvement in sprint performance (2.3%) occurred over the initial 5 m. Moreover, BR continued to enhance speed between 5 m and 10 m. Together with previous observations of improved sprint performance (Rimer et al 2015;Thompson et al 2015;Sandbakk et al 2015), these findings strengthen the evidence base for using NO 3 -as a nutritional aid to enhance aspects of sprint running performance.…”
Section: The Effect Of Br On Maximal Sprint Running Performancesupporting
confidence: 84%
“…Although previous studies have reported improved maximal sprint cycling performance (Rimer et al 2015;Thompson et al 2015) and 180 m sprint running performance (Sandbakk et al 2015) after NO 3 -supplementation, our study is the first to demonstrate that NO 3 -supplementation can improve performance during 5, 10 and 20 m sprint running by ~1-2%.…”
Section: The Effect Of Br On Maximal Sprint Running Performancecontrasting
confidence: 68%
See 1 more Smart Citation
“…In contrast, limited effects of NO 3 − supplementation have been reported for similar duration exercise tests in individuals with a greater training status (i.e. well-trained and elite athletes) (VO 2max >70 ml·kg −1 ·min −1 ) (Peacock et al 2012;Bescós et al 2012;Christensen et al 2013;Porcelli et al 2014;Sandbakk et al 2015). These highly trained athletes manifest a host of different characteristics likely to diminish their responsiveness to NO 3 − supplementation (for review, see Jones 2014), including elevated endogenous NO 3 − and NO 2 − reserves (Vassalle et al 2003).…”
Section: Effects Of Brj On 1500 M Tt Performancementioning
confidence: 99%
“…In contrast, Sandbakk et al [6] gave nitrate, nitrate plus L-arginine, or placebo to elite cross-country skiers. They found similar increases in plasma nitrite for both treatment groups, but no differences in sprint and endurance running performance.…”
mentioning
confidence: 99%